Framing Agricultural Media: An Analysis of Critical Discourse of Business CNN and CNN Indonesia using van Dijk's Theory - Andini; Rohmah Sinta Nuriyah; Janefa Astrid Endang Rahmadian (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
This study analyzes the representation of foreign workers in the United States agricultural industry using the critical discourse analysis (CDA) model by Teun A. Dijk. Using a case study from a CNN Business article titled